Framing Analysis of News Coverage of Bullying Cases in Undip Anesthesia Specialist Doctor Program (PPDS) on Kompas.com and Detik.com - Ahmad Zakiyun Nufus (CV Projurnal Mitra Publikasi, 2025)
The case of bullying in the Specialist Doctor Education Program (PPDS) in Anesthesiology at Universitas Diponegoro (Undip) became a prominent issue in the media after allegations of psychological pressure that led to fatal consequences for a program participant. The role of the mass media, especially online media such as Kompas.com and Detik.com, is crucial in framing the news related to this case. The media's framing affects how the public perceives the issue, shapes public opinion, and encourages action or policy changes from the relevant parties.This study aims to analyze how Kompas.com and Detik.com framed the coverage of the PPDS Anesthesiology Undip case. Using Robert N. Entman’s framing analysis model, this study examines framing elements such as problem definition, causes, moral evaluation, and proposed solutions in the news coverage. This research also identifies the differences and similarities in framing by both media outlets. The findings reveal distinct framing approaches between the two media outlets. Kompas.com emphasized structural issues, particularly the inadequate oversight systems and hierarchical culture within medical education. In contrast, Detik.com focused on event chronology and emotional impact. Despite these differences, both outlets consistently advocated for systemic reforms in medical education to prevent future bullying incidents. This research contributes to communication studies literature by examining media framing of sensitive social issues and provides insights for mass media organizations in delivering balanced coverage while promoting educational reform advocacy.